Thermo-mechanical properties of sugarcane bagasse-filled polyvinyl chloride composites - Wirawan, Riza (2011)
This research is an attempt to convert bagasse, an abundant waste of agricultural product, into a natural fibre/polymer composite, which is of higher economical value. Composites of sugarcane bagasse in polyvinyl chloride (PVC) matrix were produced by a compression moulding method followed by material testing to determine the mechanical and thermal properties of the composite. Tensile test, impact test, flexural test, and dynamic mechanical and thermal analysis (DMTA) were performed to both PVC and sugarcane bagasse/PVC composites in variation of fibre contents and fibre sources, which are the inner (pith) and the outer (rind) parts of sugarcane. It was observed that the tensile strength and modulus of rind/PVC composites are higher than the unfilled PVC at fibre contents of 30% and 40% , however the impact energy and thermal stability of all composites are lower than that of unfilled PVC. Further investigation was then performed to the rind/PVC composites at the fibre content of 40%. Various chemical treatments, included fibre treatment with benzoic acid, fibre treatment with sodium hydroxide, and the incorporation of poly-[methylene(polyphenyl) isocyanate] (PMPPIC) as coupling agent were carried out. Among the three chemical treatments, the incorporation of PMPPIC gave the highest tensile strength and modulus. Both tensile strength and modulus, however, are lower compared to those of untreated sugarcane bagasse-filled composite when unwashed bagasse, which contained sugar, was used, indicating that sugar give contribution to the tensile strength and modulus of the composites. Finally, the compression moulding of the untreated composite was followed by various heat treatment processes, involving slow cooling (annealing), fast cooling (quenching), and re-heating to a temperature below Tg. The effects of the thermal history were examined by the measurement of tensile strength and strain at break as well as by differential scanning calorimetry (DSC). It was observed that the heat treatments affected the strain at break of unfilled PVC significantly with less significant effect on the tensile strengths. In contrast, various tensile strengths of sugarcane bagasse PVC composites were observed after various heat treatments with less significant effect to the strain at break. In addition, recycling of the composites erase the effect of thermal history. In conclusion, sugarcane bagasse, especially the rind part has a great potential to be used as filler in a PVC matrix composite. It increases the strength and stiffness of PVC without further expensive chemical treatment. However, it should be noted that the impact strength and thermal stability of the composites are lower than those of unfilled PVC.